2021
DOI: 10.1038/s41396-021-00902-4
|View full text |Cite|
|
Sign up to set email alerts
|

Intracellular bacteria are common and taxonomically diverse in cultured and in hospite algal endosymbionts of coral reefs

Abstract: Corals house a variety of microorganisms which they depend on for their survival, including endosymbiotic dinoflagellates (Symbiodiniaceae) and bacteria. While cnidarian–microorganism interactions are widely studied, Symbiodiniaceae–bacteria interactions are only just beginning to receive attention. Here, we describe the localization and composition of the bacterial communities associated with cultures of 11 Symbiodiniaceae strains from nine species and six genera. Three-dimensional confocal laser scanning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
116
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(125 citation statements)
references
References 77 publications
8
116
1
Order By: Relevance
“…For the two anthozoan models, N. vectensis and Aiptasia, there was little difference in terms of ectodermal topography and bacterial colonization between the two organisms, both at the column and tentacle level. However, microalgal symbionts in the family Symbiodiniaceae (LaJeunesse et al, 2018) were shown to putatively contribute to the composition of coral mucus through their exudates (Brown and Bythell, 2005;Nelson et al, 2013), which affect bacterial association (Matthews et al, 2020), and Symbiodiniaceae were also shown to harbor themselves specific bacteria (Maire et al, 2021). As such, Aiptasia is a model system not only for the study of coral-algal symbiosis, but also for the study of bacterial associations and for testing the capacity for microbiome manipulation as further discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the two anthozoan models, N. vectensis and Aiptasia, there was little difference in terms of ectodermal topography and bacterial colonization between the two organisms, both at the column and tentacle level. However, microalgal symbionts in the family Symbiodiniaceae (LaJeunesse et al, 2018) were shown to putatively contribute to the composition of coral mucus through their exudates (Brown and Bythell, 2005;Nelson et al, 2013), which affect bacterial association (Matthews et al, 2020), and Symbiodiniaceae were also shown to harbor themselves specific bacteria (Maire et al, 2021). As such, Aiptasia is a model system not only for the study of coral-algal symbiosis, but also for the study of bacterial associations and for testing the capacity for microbiome manipulation as further discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that our bacterial capacity was an order of magnitude higher for symbiotic (10 5 bacterial cells/polyp) in comparison to aposymbiotic (10 4 bacterial cells/polyp) anemones. This difference may arise from the additional niche space provided by the symbiosome, which was previously shown to harbor bacteria (Ainsworth et al, 2015), and through association with Symbiodiniaceae, which harbor their own microbial community (Deines et al, 2020;Maire et al, 2021). Visualization and enumeration of cnidarian-associated bacteria is still relatively rare (Neave et al, 2017;Cooke et al, 2019), in part because of the difficulties associated with fluorescent staining techniques in corals (Wada et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential other roles of coral-associated bacteria include carbon, nitrogen and sulfur cycling, and host protection through the production of antimicrobial compounds or competition with opportunistic bacteria [15,20]. Bacteria are found in all microhabitats in a coral polyp, including the mucus [21], skeleton [22], tissue layers [23,24], gastrodermal cavity [25], the mesoglea [26], and even inside the Symbiodiniaceae cells [27]. However, only a handful of studies have compared community structure in the different body parts of the polyp [23,28,29], where a high variability across the different compartments was found.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal was to identify bacterial strains suitable for use in a microbiome engineering approach to mitigate the effects of thermal stress in E. diaphana . Given the potential role of ROS in the bleaching process and the prevalence of bacteria in and on hosts (Lesser et al ., 2004; Work and Aeby, 2014) and intracellular Symbiodiniaceae (Ainsworth et al ., 2015; Maire et al ., 2021), our focus was to select diverse E . diaphana –sourced bacterial isolates with an extracellular free radical scavenging (FRS) phenotype.…”
Section: Introductionmentioning
confidence: 99%